Assessing cutter consumption in hard rock tunneling in Singapore - Muhammad Nazir Hashim (2019)
The aim of this project is to investigate the thermal dependency of Bukit Timh granite’s CAI. Cerchar abrasivity tests will be carried out on Bukit Timah granite rock samples which were pre-heated to temperatures ranging from 25°C -800°C. 3D surface scan was done on each rock samples to observe the average elevation change after the abrasivity tests. To fully understand the micro structural changes that the rock samples undergo, scanned electron microscope were used and observations of the minerals were recorded. In addition, hardness tester was used and the hardness of the rocks subjected to the different temperatures were measured. The overall investigation reveals that there are notable changes to the CAI values of the rocks subjected to the different temperatures. Heat alters the microstructural formation as micro cracks started to initiate and the rate of propagation of the micro-cracks increases as temperature increases. Thus, due to this effect, the CAI values for the rock samples changes with different temperature treatment. However, on the other hand, the hardness of the rock samples does not show any notable changes and remains fairly constant even when the temperature treatment changes. More in depth studies and research are recommended to further improve on the understanding of the thermal effects on Bukit Timah granite’s abrasivity.